UTILIZATION OF SHRIMP SHELL WASTE INTO ORGANIC SEASONING: EMPOWERMENT OF PKK MOTHERS IN SAWOJAJAR 2 THROUGH A ZERO WASTE LIVING APPROACH - Rini Agustina; Dodit Suprianto; Tiffany Azhar Izzuddin (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Shrimp shell waste has long been merely kitchen trash discarded by housewives. Yet beneath these seemingly worthless shells lies extraordinary nutritional content. This community service activity aimed to empower PKK mothers in RT Sawojajar 2 to process shrimp shell waste into healthy, durable, and economically valuable organic seasoning. The method employed was participatory demonstration and training, where the mothers not only observed but also directly practiced the entire production process. The results showed a significant increase in knowledge: from only 2 individuals (10%) who knew how to process shrimp shells before the activity, to 18 individuals (90%) after the activity. As many as 16 out of 20 mothers (80%) expressed willingness to replace synthetic seasonings with homemade products. The products produced by the mothers were also deemed marketable, with production costs as low as IDR 7,500 per 100 grams. This activity proves that a zerowaste living approach can begin from the household kitchen, with tangible impacts on health, savings, and environmental sustainability. Keywords: Shrimp Shell, Organic Seasoning, PKK Sawojajar 2, ZeroWaste, Community Service.